Desa Toleransi: Suatu Upaya Pemberdayaan Masyarakat Dalam Membangun Gaya Hidup Bertoleransi di Desa Barang - Saputra, Andi Prasasti; Kanna, Armin Sukri (Khaliya Onomiyea: Jurnal Abdimas Nusantara, 2024)
This research results from community service conducted in Barang Village, Liliriaja District, Soppeng Regency. Through field observations, the author observed that most of society still lacks an understanding of the importance of a tolerant lifestyle. The research method used in this research is descriptive qualitative by making direct observations about the condition of the community in Barang Village. Another method used is literature study, where information regarding theoretical insight into literature can be collected through references to literature in the form of online journals and writings from trusted websites. This research aims to build values, awareness and a tolerant lifestyle in the Barang Village community. This research shows that through the work programs carried out, the community can be actively involved in implementing the values of tolerance.